PENGEMBANGAN VARIASI MODEL PERMAINAN EDUKATIF BERBASIS DEEP LEARNING PADA KOMPONEN DAYA TAHAN KEBUGARAN JASMANI MENGGUNAKAN FLIPBOOK KELAS VII - Ilma Maghfiratika; Siti Nurrochmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop and produce a digital learning medium featuring educational game model variations based on deep learning for physical fitness endurance components, packaged as a flipbook for 7th-grade students, which meets validity and instructional feasibility criteria. The method employed is Research and Development (R&D), adapting the ADDIE model modified into four main stages: Analysis, Design, Development, and Evaluation (ADDE). The implementation stage was omitted due to time constraints. Feasibility data collection was conducted using validation sheet instruments involving two subject experts: a material expert and a media expert. Quantitative data were analyzed using percentage descriptive analysis techniques, while qualitative data in the form of feedback and suggestions served as references for product revision. The results showed that the final product, an interactive digital flipbook integrating guide texts, formation images, and educational game demonstration videos, was rated as